Evidence-Based Practice and Qualitative Research: A Primer for Library and Information Professionals - Lisa Given (Evidence Based Library and Information Practice, 2007)
Objectives This paper discusses the importance of qualitative research in evidence-based library and information practice (EBLIP), with a focus on practical tips for evaluating and implementing effective qualitative research projects. Methods The paper provides a brief introduction to the nature of qualitative inquiry and its status within current models of evidence assessment. Three problems of excluding qualitative research from the evidence-base in library and information studies (LIS) are identified: 1) ignoring the social sciences and humanities traditions that inform research in the field; 2) privileging of quantitative and experimental methods over others in evidence assessment; and, 3) focusing attention away from the best evidence for LIS research problems. Results ‐ Qualitative approaches commonly used in library and information contexts are discussed, along with strategies for assessing quality in this work and some of the common ethics-related issues that researchers and professionals must consider. Conclusions ‐ LIS professionals are encouraged to: 1) select research methods – including qualitative approaches – that best suit LIS questions; 2) design collaborative projects that combine quantitative and qualitative approaches, that will address research questions in a more complete way; 3) consider qualitative measures of rigor in assessing quality – rather than imposing quantitative expectations; and 4) revise existing models of “evidence” to recognize the value and rigor of qualitative research projects.